2007
DOI: 10.1007/s10910-007-9320-0
|View full text |Cite
|
Sign up to set email alerts
|

The form of the rate constant for elementary reactions at equilibrium from MD: framework and proposals for thermokinetics

Abstract: The rates or formation and concentration distributions of a dimer reaction showing hysteresis behavior are examined in an ab initio chemical reaction designed as elementary and where the hysteresis structure precludes the formation of transition states (TS) with pre-equilibrium and internal sub-reactions. It was discovered that the the reactivity coefficients, defined as a measure of departure from the zero density rate constant for the forward and backward steps had a ratio that was equal to the activity coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…There were at least 3 different ways in which NE principles and properties were deduced in previous studies [ 3 , 6 , 9 , 81 , 82 ]. Firstly, if the PLE is assumed as a strong principle [ 26 , 28 , 76 ], then thermostatic potentials such as given by [ 70 ] for NE systems and using time comparisons for irreversible and reversible transitions (Eq 33 [ 3 ]) e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There were at least 3 different ways in which NE principles and properties were deduced in previous studies [ 3 , 6 , 9 , 81 , 82 ]. Firstly, if the PLE is assumed as a strong principle [ 26 , 28 , 76 ], then thermostatic potentials such as given by [ 70 ] for NE systems and using time comparisons for irreversible and reversible transitions (Eq 33 [ 3 ]) e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We refer toP i as any variable that is a function of k constructed on physical or mathematical grounds, and not just to the special case defined in (6). Write…”
Section: Details Of Methods (I)amentioning
confidence: 99%
“…λ ∞ and Y ∞ ) if k, the rate constant is the single optimizing variable in this approximation in a single step, unlike conventional methods. We assume here that the rate laws and rate constants are not slowly varying functions of the reactant or product concentrations, which has recently from simulation studies been shown to be generally not the case [6]. The first order reaction studied here is the methanolysis of ionized phenyl salicylate with data derived from the literature [7, Table 7.1, p.381] which can be represented as…”
Section: Applications In Chemical Kineticsmentioning
confidence: 99%
“…λ ∞ and Y ∞ if k, the rate constant is the single optimizing variable in this approximation. We assume here that the rate laws and rate constants are not slowly varying functions of the reactant or product concentrations, which has recently from simulation been shown to be generally not the case [21]. Under this standard assumption, the rate equations below all obtain.…”
Section: Applications In Chemical Kineticsmentioning
confidence: 99%